The Effect Capital Adequacy, Liquidity and Credit Risk to Profitability of Commercial Banks - Chairunnisah Ramadhanti; Marlina; Siti Hidayati (Journal of Economics, Business, and Government Challenges, 2019)
This study aims to determine the effect of Capital Adequacy proxied with Capital Adequacy Ratio (CAR), Liquidity proxied by Loan to Deposit Ratio (LDR), and Credit Risk proxied by Non Performing Loans (NPL) toward Profitability proxied by Return on Asset (ROA). Population in this study are banking companies listed on the Indonesia Stock Exchange (IDX) 2015-2017. The technique of determination of the sample using the method of purposive sampling and obtained 27 banking companies with a research period of three years to obtain 81 units of samples. Data analysis was done using Microsoft Excel 2010 and hypothesis testing in this research using Data Panel Regression Analysis with the E-Views 9.0 program and a significance level of 5%. The results of the research shows that (1) capital adequacy (CAR) has a significant positive effect on profitability (ROA), (2) liquidity (LDR) has a positive and significant effect on profitability (ROA), (3) credit risk (NPL) has a negative effect and significant to profitability (ROA).